2016
DOI: 10.1001/jamainternmed.2015.6828
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Needlestick and Sharps Injuries Among Training Residents

Abstract: Needlestick and sharps injuries (NSIs), a common occupational hazard for health care workers, are serious due to seroconversion risk. According to the US Centers for Disease Control and Prevention, more than 385 000 needlestick injuries occur annually among US hospital employees. 1 Current research on residents is sparse and conflic ting. Needlestick and sharps injuries have been reported highest during the first postgraduate year (PGY), 2-5 but studies have relied on self-reported data or a small sample of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Likewise, Lee JJ et al reported that needlestick injury events tend to occur in interns with lesser clinical skill and occur during a period when new interns and residents join the clinic [21]. Other studies have identified similar findings [22, 23]. …”
Section: Discussionmentioning
confidence: 94%
“…Likewise, Lee JJ et al reported that needlestick injury events tend to occur in interns with lesser clinical skill and occur during a period when new interns and residents join the clinic [21]. Other studies have identified similar findings [22, 23]. …”
Section: Discussionmentioning
confidence: 94%
“…The frequency of injury is six times greater in surgical trainees compared to medical trainees. 5,9,10 We had 31 of 105 program respond to our survey, with a 63% response rate. Our study found that 68.6% of surveyed otolaryngology residents at all years of training sustained at least one NSI during their residency, which is slightly lower than a previous study of general surgery residents reported at 83%.…”
Section: Discussionmentioning
confidence: 99%
“…Marnejon et al 26 provide more information regarding the exposure of residents to accidental injury during postgraduate education. In 2000–2014, Marnejon et al recorded 129 needlestick and sharps injuries among the studied group of 924 residents.…”
Section: Hiv Risk Among Health Care Workersmentioning
confidence: 99%
“…Fortunately, there was no seroconversion in any of the cases, although 16 patients were infected with hepatitis C virus (HCV) and one with HBV. 26 …”
Section: Hiv Risk Among Health Care Workersmentioning
confidence: 99%
See 1 more Smart Citation